5 years of Dutch eco-driving: Managing behavioural change. (April 2017) - Luijt, Ralph S.; van den Berge, Maarten P.F.; Willeboordse, Helen Y.; Hoogenraad, Jan H.
Abstract: In the past years a new management approach has been developed to stimulate and monitor energy savings at the largest Dutch Train Operating Company (TOC), Nederlandse Spoorwegen (NS). This so called "Energie Zuinig Rijden" (EZR), or eco-driving approach has led to yearly energy savings of up to 5% from 2010 to 2015. The EZR approach is a bottom-up approach which intends to bring about behavioural change. This approach starts by teaching the drivers an eco-driving method, then coaching driver managers into enhancing performance, and finally involving regional managers in setting, and upholding realistic energy saving targets. The EZR approach has proven to be successful in bringing about the necessary changes to run a more energy-efficient TOC. To support the management, an energy saving monitor has been developed, and implemented. This monitor measures the amount of energy savings per team of 30 drivers on a monthly basis. Thus giving feedback to the managers, and enabling them to take additional actions in order to enhance performance.